Neuron-autonomous susceptibility to induced synuclein aggregation is exacerbated by endogenous Lrrk2 mutations and ameliorated by Lrrk2 genetic knock-out. Issue 1 (7th January 2020) - MacIsaac, Sarah; Quevedo Melo, Thaiany; Zhang, Yuting; Volta, Mattia; Farrer, Matthew J; Milnerwood, Austen J
Abstract: Neuronal aggregates containing α-synuclein are a pathological hallmark of several degenerative diseases; including Parkinson's disease, Parkinson's disease with dementia and dementia with Lewy bodies. Understanding the process of α-synuclein aggregation, and discovering means of preventing it, may help guide therapeutic strategy and drug design. Recent advances provide tools to induce α-synuclein aggregation in neuronal cultures. Application of exogenous pre-formed fibrillar α-synuclein induces pathological phosphorylation and accumulation of endogenous α-synuclein, typical of that seen in disease. Genomic variability and mutations in α-synuclein and leucine-rich repeat kinase 2 proteins are the major genetic risk factors for Parkinson's disease. Reports demonstrate fibril-induced α-synuclein aggregation is increased in cells from leucine-rich repeat kinase 2 pathogenic mutant (G2019S) overexpressing mice, and variously decreased by leucine-rich repeat kinase 2 inhibitors. Elsewhere in vivo antisense knock-down of leucine-rich repeat kinase 2 protein has been shown to protect mice from fibril-induced α-synuclein aggregation, whereas kinase inhibition did not. To help bring clarity to this issue, we took a purely genetic approach in a standardized neuron-enriched culture, lacking glia. We compared fibril treatment of leucine-rich repeat kinase 2 germ-line knock-out, and G2019S germ-line knock-in, mouse cortical neuron cultures with those from littermates. We found leucine-rich repeat kinase 2 knock-out neurons are resistant to α-synuclein aggregation, which predominantly forms within axons, and may cause axonal fragmentation. Conversely, leucine-rich repeat kinase 2 knock-in neurons are more vulnerable to fibril-induced α-synuclein accumulation. Protection and resistance correlated with basal increases in a lysosome marker in knock-out, and an autophagy marker in knock-in cultures. The data add to a growing number of studies that argue leucine-rich repeat kinase 2 silencing, and potentially kinase inhibition, may be a useful therapeutic strategy against synucleinopathy. Abstract : aSyn-PFFs produce phosphorylated aSyn (pSyn) accumulation in cortical neuron axons. A few (∼5% green fluorescent protein-filled or unfilled) neurons have large somatic pSyn aggregates. LRRK2 knock-out cells have fewer axonal aggregates and trend to fewer cell bodies with aggregates, but those that do have similar levels of pSyn as wild-type. G2019S LRRK2 knock-in cells have more axonal aggregates, more numerous cells with somatic aggregates and trend to more pSyn within those that do. Graphical Abstract: